A Comparison of the Pharmacokinetics and Drug Safety Among East Asian Populations. (May 2014) - Oishi, Masayo; Hiro, Shintaro; Matsuoka, Nobushige; Hotta, Shinichi; Ono, Ryosuke; Mori, Yuko; Takenaka, Nobuko; Uchikawa, Yoko; Arakawa, Akio; Yuasa, Hirotoshi; Ishibashi, Taro; Miyoshi, So; et al.
Global clinical studies conducted in various countries and regions are increasing. Race and extrinsic ethnic factors are key covariates that may affect the pharmacokinetics (PK), efficacy, and safety of the drug. Genetic similarity among East Asian populations has been confirmed; thus, PK, efficacy, and safety in these populations are expected to be similar, but this has not been confirmed. This study presents a comparison of PK and safety among East Asians from clinical studies sponsored by Pfizer. Four compounds with different characteristics, including mechanism of actions and PK profiles, were selected, and retrospective PK and safety comparisons in East Asians were conducted. No distinct differences were observed in PK and safety across the 4 compounds. These results are consistent with previous reports on PK comparisons and meet the expectations based on genetic similarity among East Asians. Extrapolation of these findings to other compounds should be done with caution, but these results should support the consideration of mutual use of clinical data among East Asian countries.